Ancestral Imprints : Histories of Irish Traditional Music and Dance - Smith, Therese, 1959- (Book collections on Project MUSE., 2012)
This book is about the history and practice of recording Irish traditional music and dance, and the variety of documents that exist as a result of the activities of collectors both in Ireland and in North America.